(untitled) (Research, Society and Development, 2020)
This study aimed to understand the teaching process applied to the theme Cell Biology in public high schools in Barreirinhas. The study interviewed 4 Biology teachers, from three public schools (two state and one federal), teachers of Cell Biology content in the first year of high school. The results showed that of the three teaching units surveyed, only one had a laboratory structure for carrying out practical classes on the problematic theme, and this space is still very deficient in materials. Regarding teaching methodologies, applied to Cell Biology, with students, these were described as an expository and dialogued class, application of dynamics, parodies, group work, games and making prototypes of cells and microscopes, in addition to traditional means such as evidences. The teaching process of Cell Biology in the High School of Barreirinhas, Maranhão, still presents demands to be overcome, although the applied teaching methodologies already present progressive characteristics, in parts.